1970
DOI: 10.1002/pssb.19700390109
|View full text |Cite
|
Sign up to set email alerts
|

On the Theory of Hot Luminescence and Resonant Raman Effect of Impurity Centres

Abstract: For a n impurity centre the resonant secondary radiation spectrum, consisting of luminescence, Raman scattering, hot luminescence, and interference terms, is studied a t low temperatures using the model of one local or pseudolocal mode, active in the electronic transition and taking into account the change of the equilibrium position and frequency of this mode. It is shown that the latter plays an essential role in the problem of the classification of the resonant Raman scattering and hot luminescence. The ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
4

Year Published

1971
1971
2001
2001

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 81 publications
(11 citation statements)
references
References 4 publications
0
7
0
4
Order By: Relevance
“…It has been observed that the phonon fluctuations generally have an energy spectrum extending up to ∼100 cm –1 with a peak at about several dozens of cm –1 27, 28. This means that interaction with phonons in proteins decays in a time of about h /(∼100 cm –1 ) ≈ 0.3 ps since it gives the order of the dephasing and thermalization time among phonons, where h represents the Planck constant 29–33. This has indeed been observed as a rapid decay of protein distortion, in a time of ∼0.36 ps, in association with electron transfer in a blue‐copper protein, plastocyanin, by direct time‐domain measurements 34, 35.…”
Section: Eet From the B800 To B850 Ring In Lh2mentioning
confidence: 91%
“…It has been observed that the phonon fluctuations generally have an energy spectrum extending up to ∼100 cm –1 with a peak at about several dozens of cm –1 27, 28. This means that interaction with phonons in proteins decays in a time of about h /(∼100 cm –1 ) ≈ 0.3 ps since it gives the order of the dephasing and thermalization time among phonons, where h represents the Planck constant 29–33. This has indeed been observed as a rapid decay of protein distortion, in a time of ∼0.36 ps, in association with electron transfer in a blue‐copper protein, plastocyanin, by direct time‐domain measurements 34, 35.…”
Section: Eet From the B800 To B850 Ring In Lh2mentioning
confidence: 91%
“…30A, 521 (1969). 6 It is noted that the corresponding minimum in Si shifts clearly to higher stress with increasing power input. These observations will be discussed further in a forthcoming paper.…”
mentioning
confidence: 94%
“…In the case of degenerate electronic states, the main problem in the calculation of the Fourier amplitude [Eqn (7)] is that the operators [ V , ( V , HI)] and V do not commute because the vibronic matrix V is offdiagonal. Here we assume that the off-diagonal terms of the matrix V are small, i.e.…”
Section: Weak Coupling With Non-totally Symmetric Off-diagonal (Transmentioning
confidence: 99%
“…It is shown in the Appendix that at T # 0, RRS can be expanded into different orders in such a way that for any given order of RRS the Raman cross-section is determined by the square of the absolute value of the corresponding temperature-averaged Raman amplitude. Hence Fourier transformation of the first-order Stokes RRS gives A y @ ) = i 0 ( Z ) ( r i j + q -1 ' 2 x (exp(i.rH,)M, exp(izH,)M, (7) The Fourier transform of the anti-Stokes RRS can be obtained from the Stokes component as2' Expressions for an arbitrary order RRS Fourier amplitude are given in the Appendix.…”
Section: Fourier Amplitudes Of Rrsmentioning
confidence: 99%
See 1 more Smart Citation